ANALISIS PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG DENGAN WORD OF MOUTH POSITIF SEBAGAI VARIABEL MODERASI - Sumaryanto, Muhammad Rizky Saleh Tabalema, Untung Sriwidodo & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The object of this study is to determine the significance effect of Brand Image on smartphone Samsung buying decisions; Positive Word of Mouth influences on smartphone Samsung buying decisions; Positive Word of Mouth influences on the moderation of Brand Image to the smartphone Samsung buying decisions. The population of this study was the Economics Faculty students, University Slamet Riyadi Surakarta using smartphone Samsung, by employing 100 respondents using accidental sampling technique. The technique of collecting data used questionnaires instrument through the stages of testing of validity and reliability first. Test requirements regression used classical assumption. Data were analyzed using double linear regression analysis and absolute difference. The results showed that Brand Image significantly influences on smartphone Samsung buying decisions made by students of the Economics Faculty, University of Slamet Riyadi Surakarta; Positive Word of Mouth is not significant influence smartphone Samsung buying decisions made by made by students of the Economics Faculty, University of Slamet Riyadi Surakarta. Positive Word of Mouth is not moderate the Brand Image of the smartphone Samsung buying decisions made by students of the Economics Faculty, University of Slamet Riyadi Surakarta.Keywords: Brand Image, Positive Word of Mouth, buying decisions.